Evaluation of neurotransmitters (Gamma-aminobutyric acid and serotonin) and apoptosis factor (Caspase-7) as biomarkers for the diagnosis of autism spectrum disorder - Hameed, Noor Ahmed; Hassan, Shrouk Abd Alrazak; Abbas, Hamid Jaddoa (Edelweiss Applied Science and Technology, 2024)
Autism spectrum disorder (ASD) is a neurodevelopmental disability characterized by impaired communication and social skills along with restricted interests and repetitive behaviors. Biomarkers such as γ-aminobutyric acid (GABA), serotonin (5-Hydroxytryptamine, 5-HT) and caspase-7, showing potential for early diagnosis and management of ASD. To evaluate the effectiveness of GABA, serotonin and caspase-7 as novel biomarkers to predict autism at an early stage. A case- control study which started from November 2023 to June 2024, that involved 77 children’s patients, newly diagnosed with autism. The control group was comprised of 61 age- and sex-matched apparently healthy children, they had no history of autism and any other chronic diseases. Serum samples were analyzed for GABA, serotonin and caspase-7 by using enzyme linked immune-sorbent assay (ELISA) technique. The statistical package for social sciences (SPSS- 26) was used for data analyses. The study revealed significantly elevated GAMA and caspase-7 levels; while, no significant differences of serotonin level between the autistic children’s patients and the control group. This study provides a groundbreaking revelation of the biochemical markers (GAMA and caspase-7) and autism spectrum disorder, the myriad metabolic and neurochemical dysfunctions of which form a complex tapestry of ASD.